2014
DOI: 10.1152/ajpgi.00290.2013
|View full text |Cite
|
Sign up to set email alerts
|

Stress disrupts intestinal mucus barrier in rats via mucin O-glycosylation shift: prevention by a probiotic treatment

Abstract: Despite well-known intestinal epithelial barrier impairment and visceral hypersensitivity in irritable bowel syndrome (IBS) patients and IBS-like models, structural and physical changes in the mucus layer remain poorly understood. Using a water avoidance stress (WAS) model, we aimed at evaluating whether 1) WAS modified gut permeability, visceral sensitivity, mucin expression, biochemical structure of O-glycans, and related mucus physical properties, and 2) whether Lactobacillus farciminis treatment prevented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 47 publications
3
90
0
1
Order By: Relevance
“…For example, chronic subordinate colony housing, water avoidance stress, and water immersion, in rats significantly reduces the number of mucous-producing cells, thickness of the mucous barrier, and the production of the mucin Muc2 in the colon (Da Silva et al, 2014; Nyuyki et al, 2012; Shigeshiro, 2012). Thus, although it has been recognized for approximately 100 years that stress can change gastrointestinal system functioning, the extent of the effects of stressor exposure on GI functioning, as well as some of the mechanisms by which they occur, are increasingly well defined.…”
Section: Introductionmentioning
confidence: 99%
“…For example, chronic subordinate colony housing, water avoidance stress, and water immersion, in rats significantly reduces the number of mucous-producing cells, thickness of the mucous barrier, and the production of the mucin Muc2 in the colon (Da Silva et al, 2014; Nyuyki et al, 2012; Shigeshiro, 2012). Thus, although it has been recognized for approximately 100 years that stress can change gastrointestinal system functioning, the extent of the effects of stressor exposure on GI functioning, as well as some of the mechanisms by which they occur, are increasingly well defined.…”
Section: Introductionmentioning
confidence: 99%
“…The number of the positively stained goblet cells was determined for 10 full-length crypts using Image-ProPlus software, version 6.0 (Media Cybernetics). The values were averaged per crypt for each tissue sample (Da Silva et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…To this point, our laboratory recently found that forced and voluntary exercise differentially alters the microbiome in both the cecum and feces of mice. 61 Despite these findings, the regulation of mucin and bacterial dynamics are largely understudied in response to exercise, especially in humans. For example, we found that FTR significantly upregulated Ruminococcus gnavus, 35 a mucus-degrading bacteria that contains an intramolecular trans-sialidase enzyme and a Nan cluster, which together allow the bacteria to both degrade and consume terminal sialic acid residues on the mucin glycoprotein structure.…”
Section: Exercise and The Intestinal Microbiomementioning
confidence: 99%